(untitled) (Nigerian Journal of Technology, 2020)
This research examined the maintenance plans and strategies used by three airports in Nigeria to ascertain how they maintain existing infrastructure for full assets utilization and safer operational capacities. Interviews and questionnaires were employed to get concise data from all the areas and infrastructure available at Akanu Ibiam International Airport, Port Harcourt International Airport and Margaret Ekpo International Airport. Descriptive statistics and ordinal logistic regression were used in analysis and report. While Akanu Ibiam International Airport employs preventive maintenance practices on most of their facilities, Port Harcourt International Airport and Margaret Ekpo International Airport adopt corrective maintenance practices. All the airports investigated suffer poor operational efficiency, dilapidating infrastructure and facilities, and lack maintenance actions. The maintenance schedule available at Akanu Ibiam International airport can serve as a template at Port Harcourt International Airport and Margaret Ekpo International Airport. This maintenance plan must be implemented in order to achieve improvement in operational capacities. http://dx.doi.org/10.4314/njt.v39i3.13